State of the Universe 2008 : new images, discoveries and events - Ratcliffe, Martin (New York : Springer, 2008)
This annual astronomy review covers all major astronomical news on topics beyond the Solar System and includes web links for all major news stories, providing a bridge between the public news stories and the actual research web sites. The set of appendices at the end of the book include a list of launches of major astronomical observatories/satellites during the past year; a list of planned future astronomical satellites; basic data on all astronomical observatories currently in operation with web links for the reader who wishes to find out more.
Popular treatment.
Keywords: Astronomy -- Popular works; Space sciences -- Popular works